PENTNGKATAN KETERAMPILAN INDUSTRI PRODUK FIBERGLASS DI CV JAMINDO SEJAHTERA JOGYA - Siswantoyo, Siswantoyo; Sudarko, Rumpis Agus (Universitas Negeri Yogyakarta, 2005)
Smallindustrialoftenalsoreferredwiththe smallindustryowning.,.ideof rolewhen seenfromtrilogyofIndonesiadevelopment.Small-:dustrialattendancefromtimeto timehave earnedtogivetheevidencein.'.::coming emulationand abilitytolinger.Especialaspecthad by small.:Justrynamelymotivateand flexibility.Attendance ofthisinterpreneurshipsProgrammeisvery assistingto:: morepreparethenew candidatebusinessmanas accordingtoarea::'. eloped. Target of thisactivityfor exampleimprovingstudentknowledge.. :he rvorldofinterpreneurshipin areafiberglass,skilledproduce, peeping. -: idea desaign ofrelatedto its sciencearea.Amountofparticipant10,::Jent, This activit-visconductedby counted3 timesperr